Fear of progression and quality of life in patients with heart failure: a cross-sectional study on the multiple mediation of psychological distress and resilience - Cancan Chen; Xiaofei Sun; Yanting Zhang; Henan Xie; Jie Kou; Hongmei Zhang (BMC Nursing)
Abstract Background Existing research indicates that fear of progression influences the quality of life of patients with various diseases. However, the influence of fear of progression on the quality of life of patients with heart failure and its underlying mechanisms remain unclear. This study aimed to identify the link between fear of progression and quality of life in patients with heart failure and explore the multiple mediating roles of psychological distress and resilience in this association. Methods This multicenter, cross-sectional study was conducted between March and December 2023 across four tertiary hospitals in China. Data on fear of progression, psychological distress (anxiety and depression), resilience, and quality of life were collected. The PROCESS macro in SPSS was used to analyze the multiple mediation model. Results The study involved 277 patients. The total indirect effect of fear of progression on quality of life was significant. Fear of progression influenced physical quality of life through two pathways: (i) resilience independently, and (ii) psychological distress-depression and resilience serially. Additionally, fear of progression influenced mental quality of life through three pathways: (i) psychological distress (anxiety and depression) independently, (ii) resilience independently, and (iii) psychological distress (anxiety and depression) and resilience serially. However, psychological distress-anxiety or resilience had no mediating effect on the relationship between fear of progression and physical quality of life in patients with heart failure. Conclusions Fear of progression had a negative association with quality of life in patients with heart failure. In addition, the relationship between fear of progression and quality of life was mediated by psychological distress and resilience. Interventions targeting the reduction of psychological distress and enhancement of resilience may mitigate the impact of fear of progression on quality of life in patients with heart failure.